QUESTIONS OF THE FEMALE HIGHER EDUCATION ON PAGES OF THE DOMESTIC PRESS OF THE 1860-1880TH (ON THE MATERIAL OF EDITORIALS OF THE «MOSKOVSKIYE VEDOMOSTI» NEWSPAPER) - Elena V. Perevalova (Moscow Polytechnic University, 2016)
Questions of the female higher education were actively discussed in the press in the second half of the XIX century. The analysis of editorials of the conservative newspaper «Moskovskiye Vedomosti» issued by M.N. Katkov, shows that the newspaper didn't challenge the rights of women for studying at university, but considered this question indissolubly with a problem of formation of a system of highAquality secondary education for women. The "Moskovskiye Vedomosti" with deep arguments proved the need of serious preliminary preparation, obligation of a gymnasia course for girls, and also warned society against enthusiasm for «nihilism».